Advertisement Remove all ads

Solve the following for x : tan^−1((x−2)/(x−3))+tan^−1((x+2)/(x+3))=π/4,|x|<1 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Solve the following for x :

`tan^(-1)((x-2)/(x-3))+tan^(-1)((x+2)/(x+3))=pi/4,|x|<1`

Advertisement Remove all ads

Solution

 

`tan^(-1)((x-2)/(x-3))+tan^(-1)((x+2)/(x+3))=pi/4`

`=>tan^(-1)((x-2)/(x-3))+tan^(-1)((x+2)/(x+3))=tan^(-1)1`

`=>tan^(-1)((x-2)/(x-3))=tan^(-1)1-tan^(-1)((x+2)/(x+3))`

`=>tan^(-1)((x-2)/(x-3))=tan^(-1)(1-(x+2)/(x+3))/(1+(x+2)/(x+3))`

`=>tan^(-1)((x-2)/(x-3))=tan^(-1)(x+3-x-2)/(x+3+x+2)`

`=>tan^(-1)((x-2)/(x-3))=tan^(-1)1/(2x+5)`

`=>(x-2)/(x-3)=1/(2x+5)`

`=>(x-2)(2x+5)=x-3`

`=>2x^2-4x+5x-10=x-3`

`=>2x^2=7`

`=>x=+-sqrt(7/2)`

Concept: Inverse Trigonometric Functions (Simplification and Examples)
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×